Determination of Gibbs Free Energy in the Compound Formation of Li-P and Li-Fe-O by Pymatgen - Anis Yuniati; Syamsul Andry (Kaunia: Integration and Interconnection Islam and Science Journal, 2022)
The Gibbs free energy of the compound formation from a phase diagram based on Python Materials Genomic (Pymatgen) and Application Programming Interface (API) Key had been determined. The compounds shown were stable synthesized from the combination of Li-P and Li-Fe-O atoms. This stability was indicated by the value of the Gibbs free energy of the compounds formation obtained from the phase diagram of each atomic combination. The diagram was created from the integration between Python and the database from the Materials Project via an API Key using Pymatgen. From the research conducted for the combination of Li-P atoms, compounds and the Gibbs free energy of formation shown were Li3 P (-0.697 eV/atom), LiP (-0.523 eV/atom), Li3 P7 (-0.36 eV/atom), and LiP7 (-0.159 eV/atom). For Li-Fe-O combination, the compound and the energy were Li5 FeO4 (-2.117 eV/atom), LiFeO2 (-2.072 eV/atom), LiO2 (-2.067 eV/atom), Li2 FeO2 (-1.979 eV/atom), Li2 FeO3 (-1.965 eV/atom), Fe2 O3 (-1.907 eV/atom), Fe3 O4 (-1.858 eV/atom), FeO (-1.728 eV/atom), Li2 O2 (-1.651 eV/atom), and LiO8 (-0.414 eV/atom). The most stable compound from each formation was the compound with the lowest Gibbs energy, i.e Li3 P and Li5 FeO4.